Transport and social justice. Why sustainable transport is the only route to a socially just transport system. - (:unkn) unknown (My University, 2008)
As the paper argues, a social just transport system is not only a question of reducing the cost of motoring, but one of the whole car centred mobility policies prevailing. A much more socially just, equitable and forward-looking solution is to focus on increasing access to all destinations by affordable public transport, and a greatly improved environment for those travelling on footand by bike.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrspolitik; Nachhaltige Mobilität; Soziale Gerechtigkeit; Fahrradförderung